Tirzepatide - a novel dual GLP-1 and GIP receptor agonist used in pharmacotherapy of obesity: A literature review - Stachyra, Bartłomiej; Wolanin, Marta; Stawikowski, Cezary; Zielonka, Bartłomiej; Osińska, Aleksandra; Wolanin, Izabela; Madej, Karolina; Dengler, Barbara; Kowalczyk, Ilona; Krawiec, Paulina (Journal of Education, Health and Sport, 2023)
Background: Obesity is a chronic disease, which along with its complications, poses a huge threat to both our health as individuals and our healthcare as a community. Objective: The aim of this work is to review efficacy and safety of Tirzepatide, a novel dual GIP/GLP-1 receptor agonist in the treatment of obesity Method: A literature review was conducted on databases such as PubMed and Google Scholar using terms “obesity”, “obesity treatment”, “glucagon-like peptide 1”, “Glucose-dependent insulinotropic polypeptide”, “Tirzepatide” as keywords. The review was performed in accordance with the PRISMA guidelines. Results: Administration of tirzepatide once weekly provides a substantial and sustained reduction in bodyweight with little side effects. Conclusions: Clinical trials showed both high efficacy and safety of Tirzepatide in management of obesity. Due to its novel, broadened mechanism of action it seems to be the most effective drug for reducing bodyweight available on the market. Tirzepatide could be our answer to tackling the problem of world-wide obesity epidemic.